Latvian municipal budget expenditures on transport infrastructure and production in the context of improving the local economy - Komarova, Vera; Ignatjeva, Svetlana; Kudins, Janis; Kokarevica, Anita; Ostrovska, Inta; Čižo, Edmunds (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
The article aims to study Latvian municipal budget expenditures on transport infrastructure and production in the context of improving the local economy. The authors hypothesize that the comparative priority of municipal budget expenditures on two items is determined by the state of the local economy; in municipalities with a more developed economy it is ‘transport’ rather than ‘production’ budget expenses that are more likely to improve the local economy, and in municipalities with a less developed economy – vice versa. The authors tested the hypothesis based on data for 2021 and 2022 (the time after the reform of the territorial-administrative structure of Latvia) for 43 Latvian municipalities using various methods of statistical analysis. The results show that the comparative priorities in Latvian municipal budget expenditures are determined not by the state of the local economy, but rather by the geographical (or geopolitical/geoeconomical) location of the municipality. As a result of this, Latvian municipalities are grouped into territorial clusters, using the agglomeration effect from the concentration of transport infrastructure or production. Over the past year, there has been a tendency towards ‘transport-production’ economic restructuring of the territory of Latvia, the reasons for which may be geopolitical situation in the Eastern Europe.